Prospek Pengembangan Bawang Organik di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia - Adrianus Jado; Sarlina Noni (Peneliti.net, 2022)
Onion plants are one of the horticultural plants that have good prospects and include nationally excellent plants needed by residents both domestically and abroad, rich in vitamins and other important substances for human health. purpose of this research To find out the prospects of business development Oignons biologiques et connaître les facteurs moteurs et les obstacles rencontrés par la culture de l’oignon dans la pratique de jardin UNIPA.Retrait d’échantillons jusqu’à 15 personnes, en utilisant l’échantillonnage intentionnel et en utilisant l’analyse SWOT. The results showed that there is an identification of internal and external factors consisting of strengths, weaknesses, and challenges that support the prospects for the development of onion farming. 2,) the prospect of onion development is in quadrant I or aggressive strategies, which use the power to take advantage of opportunities, namely: a). utilizing research sites that are places for onion farming development by using organic fertilizers to meet consumption levels.b). Take advantage of market demand by increasing with optimal land use